Examining manifestations of power in couples: influence tactics, self-concept, and wellbeing across time - Washburn-Busk, Michelle (Kansas State University, 2020)
The purpose of this study was to examine how various influence tactics (hostility, dominance, interrogation, lecture/moralizing, denial, and assertiveness) were linked with decision-making power and individual and relationship outcomes over a four-year span of couples’ relationships. Using actor-partner interdependence mediation path modeling, I examined the use of these six observed influence tactics in a sample of 182 heterosexual dyads and found that a partner’s self-concept – particularly self-worth and perception of how much one’s partner respects them – tends to mediate the relationship between multiple influence tactics and wellbeing outcomes (depression, relationship quality, decision-making influence and satisfaction). Dominance (positive and negative forms), interrogation, hostility and lecture/moralizing related more often to individual and relational outcomes than the other influence tactics. Male lecturing/moralizing was linked with higher levels of female depression in and through lowering female self-worth, while potentially having a reverse effect for male depression and self-worth. Males feeling like their female partner respects their competencies and skills fully mediated the relationship between assertiveness and relationship quality for males and females; therefore, it may be that the male ego is a central organizing factor for heterosexual couples in established, committed relationships. Couples therapists can promote fairness in heterosexual couple relationships by assessing for, and intervening in, lecturing/moralizing and interrogation behaviors, as well as promoting affirming self-concepts and positive forms of dominance. When working with couples to promote positive communication such as assertiveness, therapists should ensure that male and female assertive behaviors serve to promote both male and females’ perception that their partner respects them, as it may be that males feeling respected may come at the expense of female relationship quality or decision-making influence.
Keywords: Power imbalances; Couples therapy; Influence tactics; Wellbeing; Self-concept; Gender